Intestinal lymphatic transport of cannabinoids: implications for people with autoimmune diseases and immunocompromised individuals - Zgair, Atheer (2017)
There has been an escalating interest in the medicinal use of Cannabis sativa in recent years. Cannabidiol (CBD) and ∆9-tetrahydrocannabinol (THC), the main constituents of Cannabis sativa, have well documented immunomodulatory effects in vitro and following administration of high doses to animals. However, these effects have not been clearly evident in humans following oral administration of cannabinoids, probably due to low systemic bioavailability. To note, cannabis and cannabis-containing medicines are currently used for symptomatic relief in autoimmune diseases, such as multiple sclerosis (MS), and in cases of immunodeficiency, such as in cancer patients on chemotherapy regimens. In this thesis, we aimed to elucidate the impact of enhancing the transport of orally administered cannabinoids to the intestinal lymphatic system, the major host of immune cells, on the immunomodulatory effects of cannabinoids. Oral administration of lipophilic cannabinoids with long-chain triglycerides (LCT) was investigated as a simple approach to enhance the intestinal lymphatic transport. The effect of LCT on the intraluminal processing of orally administered cannabinoids was assessed by means of in vitro lipolysis model. The results of in vitro lipolysis demonstrated that at least one-third of CBD dose would be solubilised and readily available for absorption to the enterocytes when orally administered in LCT-formulation. The association of CBD with chylomicrons (CM) in the enterocytes and subsequent intestinal lymphatic transport was estimated using an in silico model, in vitro association by artificial CM-like lipid particles, and ex vivo uptake by plasma-derived CM from rats and humans. The results of CM association studies revealed high intestinal lymphatic transport potential for CBD in rats and humans. Similar high lymphatic transport potential was also reported for THC in our laboratory. Oral co-administration of CBD and THC with LCT to rats increased the systemic exposure by 3-fold and 2.5-fold, respectively, compared to lipid-free formulations. The underlying mechanism of increased bioavailability is likely to enhanced intestinal lymphatic transport and decreased pre-systemic metabolism in the liver. The results of biodistribution experiments indicated that the intestinal lymphatic transport of CBD and THC was, indeed, enhanced following oral co-administration of lipids as denoted by the dramatic increase in the concentrations recovered in MLN and intestinal lymph. The concentrations of CBD and THC in intestinal lymph fluid were in the range of 120 and 60 µg/mL compared to 0.5 and 0.6 µg/mL in plasma, respectively. Moreover, CBD and THC showed dose-dependent immunosuppressive effect on lymphocytes isolated from rats and peripheral blood mononuclear cells (PBMC) isolated from humans as assessed by lymphocyte proliferation assay and flow cytometry analysis of inflammatory cytokines. These effects were only significant at concentrations achieved in the intestinal lymphatic system, but not in plasma, following oral co-administration of cannabinoids with LCT. CBD showed more immunosuppressive effects on lymphocyte proliferation and the expression of inflammatory cytokines comparing to THC. Also, PBMC from MS patients were more susceptible to the immunomodulatory effects of cannabinoids than PBMC from healthy volunteers and cancer patients on chemotherapy. In conclusion, oral administration of cannabinoids with lipids can enhance the intestinal micellar solubilisation and augment the systemic exposure to cannabinoids by enhancing intestinal lymphatic transport. The concentrations of lipophilic cannabinoids recovered in the intestinal lymphatic system were extremely high and exceeded the immunosuppressive threshold of CBD and THC. The increase in systemic exposure to cannabinoids in humans is of potentially high clinical importance as it could turn a barely effective dose of orally administered cannabis into highly effective one, or indeed a therapeutic dose into a toxic one. In addition, administering cannabinoids, in particular CBD, with a high-fat meal, as cannabis-containing food, or in lipid-based formulations could represent a valid therapeutic approach to improve the treatment of MS, or other T cell-mediated autoimmune disorders. However, in immunocompromised patients, administration of cannabinoids in this way may deepen the immunosuppressive effects.